2013
DOI: 10.1128/jb.00586-13
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Interplay between Two Independent Functions of the Small RNA Regulator SgrS in Salmonella

Abstract: Bacterial dual-function small RNAs regulate gene expression by RNA-RNA base pairing and also code for small proteins. SgrS is a dual-function small RNA in Escherichia coli and Salmonella that is expressed under stress conditions associated with accumulation of sugar-phosphates, and its activity is crucial for growth during stress. The base-pairing function of SgrS regulates a number of mRNA targets, resulting in reduced uptake and enhanced efflux of sugars. SgrS also encodes the SgrT protein, which reduces sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…The base-pairing activity of SgrS ameliorates glucose-phosphate stress by inhibiting translation and promoting degradation of the ptsG and manXYZ mRNA transcripts, thereby preventing synthesis of more sugar transporters during stress. In contrast, SgrT was shown to have no effect on sugar transporter mRNA levels, but it could still reverse growth inhibition caused by stress (9,22). These and other results suggested that SgrT acted by inhibiting glucose transporter activity (9).…”
mentioning
confidence: 47%
See 3 more Smart Citations
“…The base-pairing activity of SgrS ameliorates glucose-phosphate stress by inhibiting translation and promoting degradation of the ptsG and manXYZ mRNA transcripts, thereby preventing synthesis of more sugar transporters during stress. In contrast, SgrT was shown to have no effect on sugar transporter mRNA levels, but it could still reverse growth inhibition caused by stress (9,22). These and other results suggested that SgrT acted by inhibiting glucose transporter activity (9).…”
mentioning
confidence: 47%
“…Like many other sRNAs in bacteria, SgrS carries out base-pairing-dependent regulation of numerous mRNAs (4,(17)(18)(19)(20)(21). Less typical is the second function of SgrS, namely, encoding the 43-amino-acid protein SgrT (9,22). Unlike any other known dual-function sRNA-small protein pair, SgrS and SgrT act independently in the same pathway, albeit by different mechanisms (9,22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Growth stress caused by sugar-phosphate build-up is minimized by induction of the small regulatory RNA SgrS; aMG at 0.1 % was shown to induce sgrS 126-fold while the same concentration of 2DG induced just 36-fold (Rice & Vanderpool, 2011). SgrS-dependent reduction of the level of manXYZ mRNA also takes longer than reduction of ptsG mRNA (Balasubramanian & Vanderpool, 2013). Inability of the cells to prevent 2DG-phosphate build-up as effectively as build-up of aMG-phosphate could account for 2DG being a stronger inhibitor of biofilm growth than aMG.…”
Section: Inhibition In Rich Mediummentioning
confidence: 99%